The dual burden household and the nutrition transition paradox - Doak, C. M.; Adair, Linda S.; Bentley, M. E.; Monteiro, C.; Popkin, Barry M. (Springer, 2005)
The purpose of this study is to document the prevalence of households with underweight and overweight persons (henceforth referred to as dual burden households) and their association with income and urban residence. The explorations by urban residence and income will test whether dual burden households differ from 'underweight only' and 'overweight only' households, respectively. These comparisons are relevant to differentiating or adapting nutrition-related interventions wherever obesity and undernutrition cluster at the household level.